2009
DOI: 10.1001/archinternmed.2009.117
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Clinical Importance of Pages Sent to the Wrong Physician

Abstract: E ffective communication between health care providers is essential to patient safety and quality of care. 1-6 A retrospective study of 14 000 admissions found that communication failures were the most common cause of preventable disability or death and were nearly twice as common as those due to inadequate medical skill. 6 A major type of communication failure is sending a page to the wrong physician. Prior studies have described paging problems such as paging the wrong physician, unanswered pages, and delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…These include the inability to indicate the urgency of the message, frequent interruptions, contacting the wrong physician, and inefficiencies coordinating care across multiple disciplines and specialties. [6][7][8][9][10][11][12] Hospitals have implemented a variety of health information technology (HIT) solutions to replace the numeric pager and address these clinical communication issues, including the use of alphanumeric pagers, smartphone devices, and Web-based applications that allow clinicians to triage the urgency of issues. [13][14][15][16] Although these solutions have resolved some of the deficiencies previously identified, issues relating to the impact on the interprofessional nature of healthcare remain unaddressed.…”
mentioning
confidence: 99%
“…These include the inability to indicate the urgency of the message, frequent interruptions, contacting the wrong physician, and inefficiencies coordinating care across multiple disciplines and specialties. [6][7][8][9][10][11][12] Hospitals have implemented a variety of health information technology (HIT) solutions to replace the numeric pager and address these clinical communication issues, including the use of alphanumeric pagers, smartphone devices, and Web-based applications that allow clinicians to triage the urgency of issues. [13][14][15][16] Although these solutions have resolved some of the deficiencies previously identified, issues relating to the impact on the interprofessional nature of healthcare remain unaddressed.…”
mentioning
confidence: 99%
“…11 A recent study revealed that 14% of pages went to the wrong physician and that 47% of these errant pages warranted an urgent response. 12 In our institution, the process for a nurse to identify which physician to contact regarding a patient care issue can be complex ( Figure 1). …”
mentioning
confidence: 99%
“…In 2014, that number has increased to 92.6 % [3••]. The use of smartphones has been shown to increase communication among medical providers and nurses, leading to reduction in medical errors [4]. One study showed improved efficiency when using smartphones as opposed to pagers as a means of communication between various members of the healthcare field.…”
Section: Introductionmentioning
confidence: 99%